Entrepreneurship and Digital Marketing Skills to Create an Independent and Competitive Young Generation - Padilah , Syifa Nur; Tita Puspita Sari; Rama Helmi Rianto; Melina Kurnia Sari; Nadila Istiqomah; Nunung Nurjanah; Ervina Aulia; Oksa Wellen; Ismanda Gita; Dina Fitriana; Dini Fitriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This activity is a form of dedication to one of the important aspects of the Tri Darma of Higher Education, namely community service. Apart from fulfilling responsibilities, this activity aims to make a meaningful contribution to the development and application of knowledge in society, with the main focus on SMPIT Darul Hasani students. To achieve this goal, a combination of effective learning methods is used, namely expository and inquiry. The expository method is applied through oral delivery of material, providing a strong knowledge base about entrepreneurship and digital marketing. Meanwhile, the inquiry method encourages students to think critically and analytically, dig deeper into the concept of entrepreneurship, and analyze various types of businesses and innovative ideas. As a concrete example, the success story of Nadia Istikomah's meatball business